2021
DOI: 10.1186/s12913-021-06071-6
|View full text |Cite
|
Sign up to set email alerts
|

A human factors intervention in a hospital - evaluating the outcome of a TeamSTEPPS program in a surgical ward

Abstract: Background Patient safety in hospitals is being jeopardized, since too many patients experience adverse events. Most of these adverse events arise from human factors, such as inefficient teamwork and communication failures, and the incidence of adverse events is greatest in the surgical area. Previous research has shown the effect of team training on patient safety culture and on different areas of teamwork. Limited research has investigated teamwork in surgical wards. The aim of this study was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
2
20
0
Order By: Relevance
“…The participants experienced an impact of the team training program on the ward's patient safety culture in forms of a higher level of awareness about how to work together as a team and openly communicate within and between professional groups. This is also supported by both qualitative [14] and quantitative research results from studying the implementation of the current team training program [27,28]. Our study results further indicate that the implementation process maintained psychological safety at the ward, which, according to Edmondson [29], is needed to improve patient safety.…”
Section: Discussionsupporting
confidence: 79%
“…The participants experienced an impact of the team training program on the ward's patient safety culture in forms of a higher level of awareness about how to work together as a team and openly communicate within and between professional groups. This is also supported by both qualitative [14] and quantitative research results from studying the implementation of the current team training program [27,28]. Our study results further indicate that the implementation process maintained psychological safety at the ward, which, according to Edmondson [29], is needed to improve patient safety.…”
Section: Discussionsupporting
confidence: 79%
“…Six studies involved interventions [ 24 , 25 , 26 , 27 , 28 , 29 ]. One of these intervention studies reported greater improvement than the others [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other intervention studies also reported improvements, but these were generally weaker and reported a shorter intervention period. Aaberg et al [ 24 , 28 ] found improvement in three HSOPSC dimensions in their two studies: “Teamwork within unit”, “Manager expectations and actions promoting patient safety”, and “Communication openness”. Storm et al [ 27 ] focused their interventions at the interorganizational level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations